2018
DOI: 10.3892/ol.2018.8563
|View full text |Cite
|
Sign up to set email alerts
|

Solanine reverses multidrug resistance in human myelogenous leukemia K562/ADM cells by downregulating MRP1 expression

Abstract: Abstract. Multidrug resistance (MDR) in leukemia cells is a major obstacle to chemotherapeutic treatment. High expression and constitutive activation of multidrug resistance protein 1 (MRP1) has been associated with the development of resistance to anticancer drugs in a number of tumor types. The activity of c-Jun N-terminal kinase 1 (JNK1) is associated with the occurrence of MDR and MRP1 expression. The present study aimed to investigate the ability of solanine to resensitize the Adriamycin ® (ADR)-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Solanine also inhibits the proliferation of human prostate cancer xenografts in nude mice by significantly inhibiting the mRNA and protein expression of cyclin D1, cyclin E1, cyclin dependent kinase 2 (CDK2), CDK4 and CDK6 in vivo ( 11 , 12 ). A number of studies have confirmed that solanine has strong anti-cell proliferation effects on leukemia ( 13 , 14 ), endometrial cancer ( 15 ), liver cancer ( 16 , 17 ), esophageal cancer ( 18 ), pancreatic cancer ( 19 ) and so on ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solanine also inhibits the proliferation of human prostate cancer xenografts in nude mice by significantly inhibiting the mRNA and protein expression of cyclin D1, cyclin E1, cyclin dependent kinase 2 (CDK2), CDK4 and CDK6 in vivo ( 11 , 12 ). A number of studies have confirmed that solanine has strong anti-cell proliferation effects on leukemia ( 13 , 14 ), endometrial cancer ( 15 ), liver cancer ( 16 , 17 ), esophageal cancer ( 18 ), pancreatic cancer ( 19 ) and so on ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, studies have pointed out that the growth arrest specific 5 (GAS5)/miR-18a axis is another important mechanism promoting the radiosensitivity of prostate cells ( 12 ). In the study of leukemia, solanine increases the chemical sensitivity of acute lymphocytic leukemia to doxorubicin, and reverses multidrug resistance in chronic myelogenous leukemia cells by downregulating multidrug resistance protein 1 (MRP1) expression ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…It increases the level of Bax and reduces Bcl-2 mRNA and protein levels. Furthermore, SN increases the chemosensitivity of these cells to adriamycin ( Yi et al, 2018a ) and reverses the multidrug resistance of human myelogenous leukemia (ML) K562/ADM cells ( Yi et al, 2018b ). Treatment with this compound reduces cell proliferation, leads to higher concentrations of adriamycin in cells, and reduces the expression of the MRP1 protein dependent on the JNK pathway ( Yi et al, 2018b ).…”
Section: Antitumor Effects Of Solanaceae Glycoalka...mentioning
confidence: 99%
“…For instance, emodin can reverse the drug resistance of K562 / ADM cells by inhibiting the expression of P -glycoprotein, which suggests that emodin is still potentially effective reversal agents in the treatment of chronic myeloid leukemia resistance [13]. solanine [14]and germacrone [15]were able to MDR. Through inhibiting the expression of P -glycoprotein and MRP, increasing the concentration of chemotherapeutic drugs in chronic myelogenous leukemia resistant cell lines and enhancing the cytotoxicity of drugs.…”
Section: Introductionmentioning
confidence: 99%